Identitas nasional di era globalisasi: tantangan dan upaya mempertahankan jati diri bangsa - azzahra, najwa alivia (Maliki Interdisciplinary Journal, 2026)
Indonesia’s diversity makes national identity an important aspect in maintaining social unity. In the current era of globalization, the development of technology and social media has made foreign cultures easier to enter everyday life, especially among the younger generation. This condition has caused some people to become more interested in foreign cultures than in their own local traditions. If not addressed properly, it may reduce the sense of nationalism and gradually weaken Indonesia’s national identity. This paper discusses the importance of national identity and various efforts that can be made to preserve the nation’s character amid the development of globalization. The method used in this paper is literature study by utilizing various sources such as books, journals, and scientific articles related to national identity, nationalism, and globalization. Based on the discussion, national identity still has an important role in the life of Indonesian society. In addition, civic education, preservation of local culture, and the wise use of technology can become efforts to maintain national identity in the midst of globalization. Therefore, awareness from society, the government, and educational institutions is needed to preserve national values so that they do not fade due to the influence of foreign cultures.